And wrote my story anyway : black South African women's novels as feminism - Boswell, Barbara (Wits University Press, 2021)
Part literary history, part feminist historiography, Barbara Boswell's And Wrote My Story Anyway: Black South African Women's Novels as Feminism examines ten novels and places them in a conversation with each other. The result is an arc of feminist criticism speaking forcefully to racist, white-dominated, patriarchal power.